2012
DOI: 10.1002/jcb.24063
|View full text |Cite
|
Sign up to set email alerts
|

The PPARδ ligand L‐165041 inhibits vegf‐induced angiogenesis, but the antiangiogenic effect is not related to PPARδ

Abstract: Peroxisome proliferator-activated receptor (PPAR)δ is known to be expressed ubiquitously and involved in lipid and glucose metabolism. Recent studies have demonstrated that PPARδ is expressed in endothelial cells (ECs) and plays a potential role in endothelial survival and proliferation. Although PPARα and PPARγ are well recognized to play anti-inflammatory, antiproliferative, and antiangiogenic roles in ECs, the general effect of PPARδ on angiogenesis in ECs remains unclear. Thus, we investigated the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In contrast, secretion of VEGF was increased in a human colon cancer cell line by knockdown of PPARβ/δ, and ligand activation of PPARβ/δ inhibited secretion of VEGF, an effect that was mitigated by knockdown of PPARβ/δ [20]. Examination of human umbilical vein endothelial cells (HUVEC) cells revealed that L165041 also inhibits VEGF protein expression, tube formation and HUVEC proliferation and migration, and angiogenesis in vivo [40, 41]. However, the decrease is VEGF secretion and HUVEC migration were not mediated by PPARβ/δ, in one study [41].…”
Section: Modulating Hallmarks and Enabling Characteristics Of Cancer mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, secretion of VEGF was increased in a human colon cancer cell line by knockdown of PPARβ/δ, and ligand activation of PPARβ/δ inhibited secretion of VEGF, an effect that was mitigated by knockdown of PPARβ/δ [20]. Examination of human umbilical vein endothelial cells (HUVEC) cells revealed that L165041 also inhibits VEGF protein expression, tube formation and HUVEC proliferation and migration, and angiogenesis in vivo [40, 41]. However, the decrease is VEGF secretion and HUVEC migration were not mediated by PPARβ/δ, in one study [41].…”
Section: Modulating Hallmarks and Enabling Characteristics Of Cancer mentioning
confidence: 99%
“…Examination of human umbilical vein endothelial cells (HUVEC) cells revealed that L165041 also inhibits VEGF protein expression, tube formation and HUVEC proliferation and migration, and angiogenesis in vivo [40, 41]. However, the decrease is VEGF secretion and HUVEC migration were not mediated by PPARβ/δ, in one study [41]. While it is not clear that VEGF is a bona fide PPARβ/δ target gene, there is strong evidence that ANGPTL4 is directly regulated by ligand activation of PPARβ/δ, and also by PPARα and PPARγ [42].…”
Section: Modulating Hallmarks and Enabling Characteristics Of Cancer mentioning
confidence: 99%
“…Confirming these data, L-165041 was found to inhibit VEGF-stimulated angiogenesis by suppressing the cell cycle progression independently of PPAR δ : in particular, it reduces the number of endothelial cells in the S phase and the expression levels of cell cycle regulatory proteins such as cyclin A, cyclin E, cyclin-dependent kinase (CDK) 2, and CDK4 [36]. Furthermore, a recent in vitro study found that L-165041 significantly inhibits high glucose-induced interleukin-6 and TNF- α production, receptor for advanced glycation end products expression, and NF- κ B translocation in human embryonic kidney 293 (HEK) cells; in addition, it increases superoxide dismutase expression and attenuates apoptosis in HEK and mesangial cells [37].…”
Section: The Role Of Pparβ/δ In Metabolic Diseasesmentioning
confidence: 90%
“…Of M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 note, at these high concentrations the PPARD ligands have been shown to also activate PPARA and PPARG [9,10]. Interestingly, a recent study by Park et al demonstrated that the PPARD agonist L-165041 suppresses the cell cycle progression in ECs independently of PPARD since siRNA targeting PPARD could not reverse the anti-angiogenic effect of L-165041 [11]. In summary, these studies suggest that PPARD is pro-angiogenic and that the anti-angiogenic effects are PPARD-independent and probably due to off target effects specific to the compound in question.…”
Section: Endothelial Cells M a N U S C R I P Tmentioning
confidence: 98%